Increased light availability due to forestry mowing of invasive European buckthorn promotes its regeneration. Issue 2 (5th February 2020) - Anfang, Carl; Schuster, Michael J.; Wragg, Peter D.; Reich, Peter B.
Abstract : The invasive shrub Rhamnus cathartica L. (common buckthorn) dominates the understory of many temperate forests of eastern North America. Common buckthorn outcompetes native understory species for light, forming monospecific stands that suppress plant and animal diversity. Removing common buckthorn is a common management priority within its invasive range. In recent years, forestry mowing has become popular in removing common buckthorn. This control method removes a midstory of common buckthorn, increasing light availability to the lower understory (which could favor buckthorn regeneration) and creating a layer of mulch on the forest floor (which could suppress buckthorn regeneration). Here we investigate whether and how increased light availability and increased ground cover (mulch) resulting from forestry mowing affects buckthorn regeneration from the seed bank. We evaluated buckthorn germination, survival, and early growth in response to a factorial combination of shading treatments and buckthorn mulch depth treatments in an oak forest in Minnesota, U.S.A. Increased light availability increased buckthorn seedling survival and growth, whereas increased mulch depth did not significantly affect the number of buckthorn establishing from seed over one growing season and winter. Thus, removing buckthorn by forestry mowing (or any other method) is likely to facilitate buckthorn reestablishment by increasing light availability at the ground.